Performance Improvement of Graphene/Silicon Photodetectors Using High Work Function Metal Nanoparticles with Plasma Effect. Issue 9 (27th February 2018) - Hu, Ming; Yan, Yucong; Huang, Kun; Khan, Afzal; Qiu, Xiaodong; Xu, Dikai; Zhang, Hui; Yu, Xuegong; Yang, Deren
Abstract: Graphene/silicon (Gr/Si) photodetectors have attracted much attention recently for their simple fabrication and satisfactory performance. However, the responsivity is relatively low compared to other visible detectors. Herein, plasma effects are induced to enhance the photon absorption by covering random platinum nanoparticles (Pt NPs) on top of the devices. Consequently, a stronger built‐in electric field in the Gr/Si photodetectors is generated due to the high work function of Pt. Their responsivity can reach up to 1.68 × 10 7 AW −1, which is one order of magnitude higher than the pristine devices. Furthermore, the response time is found to be less than 180 ns because of low trap states density at interface. The obtained results suggest a facile and universal way to optimize the performance of Gr/Si photoelectric devices. Abstract : After covering platinum nanoparticles on graphene/silicon by a facile method, the responsivity of graphene/silicon photodetectors increases by an order of magnitude, which is the highest reported so far among graphene‐based photoconductors.